2020
DOI: 10.1186/s13071-020-04497-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential vector competence of Ornithodoros soft ticks for African swine fever virus: What if it involves more than just crossing organic barriers in ticks?

Abstract: Background Several species of soft ticks in genus Ornithodoros are known vectors and reservoirs of African swine fever virus (ASFV). However, the underlying mechanisms of vector competence for ASFV across Ornithodoros species remain to be fully understood. To that end, this study compared ASFV replication and dissemination as well as virus vertical transmission to descendants between Ornithodorosmoubata, O. erraticus, and O. verrucosus in relation to what is known about the ability of these sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…aegypti [ 20 ]. A comparative study of vector competence of different Ornithodoros species ( O. moubata , O. erraticus and O. verrucosus ) using several strains of ASFV showed variable infection rates depending on the tick–virus pairs assessed [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…aegypti [ 20 ]. A comparative study of vector competence of different Ornithodoros species ( O. moubata , O. erraticus and O. verrucosus ) using several strains of ASFV showed variable infection rates depending on the tick–virus pairs assessed [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the variety of ASFV strains used to test the virucidal activity of chemical compounds, it emerged that these are limited to the use of genotype I and Vero-adapted ASFV strains such as the BA71V and Lisbon 60 strains. Few studies tested field ASFV strains [24,26,27,30,33,35] belonging to genotype I and II and only one study used a field ASFV belonging to genotype VIII [40]. Regarding the virulence and hemadsorption characteristics of the ASFV tested, no data is available.…”
Section: Discussionmentioning
confidence: 99%
“…In this context it is interesting to mention that Pereira De Oliveira et al observed higher susceptibility for ASFV infection in a long-time lab-reared colony of O. moubata compared to field collected Ornithodoros sp. [ 58 ]. They hypothesized that lab-reared ticks are highly inbred with fixed alleles and have a poor microbiome, resulting in a poorly stimulated or even immunologically naïve immune system compared to ticks collected from the field; (iii) represent non-coding RNA (ncRNA) sequences.…”
Section: Discussionmentioning
confidence: 99%